1983
DOI: 10.1007/bf00407765
|View full text |Cite
|
Sign up to set email alerts
|

Methyltransferases involved in methanol conversion by Methanosarcina barkeri

Abstract: 2-(Methylthio)ethanesulfonate (CH3S-CoM) is formed as an intermediate in methanogenesis from methanol by cell-free extracts of Methanosarcina barkeri. The enzyme system involved in the methyl transfer from methanol to 2-mercaptoethanesulfonate (HS-CoM) was resolved into two enzyme fractions. One enzyme (methanol:5-hydroxy-benzimidazolylcobamide methyltransferase) appears to be a cobalamin-containing protein, which is oxygen sensitive. The other enzyme (Co-methyl-5-hydroxybenzimidazolylcobamide: HS-CoM methyltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
106
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(109 citation statements)
references
References 23 publications
3
106
0
Order By: Relevance
“…In acetogenic and methanogenic organisms, association of enzyme components essential for either synthesis of acetate or for the conversion of acetate to methane has been proposed [3,6,11,12]. Hu et al [6] have suggested that the corrinoid and CODH from the acetogen, Clostridium thermoaceticum, may form a complex in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In acetogenic and methanogenic organisms, association of enzyme components essential for either synthesis of acetate or for the conversion of acetate to methane has been proposed [3,6,11,12]. Hu et al [6] have suggested that the corrinoid and CODH from the acetogen, Clostridium thermoaceticum, may form a complex in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al [6] have suggested that the corrinoid and CODH from the acetogen, Clostridium thermoaceticum, may form a complex in vivo. In Methanobacterium barkerii, the efficient transfer of methyl group from methanol to HS-CoM appears to require a multi-enzyme complex [12]. The suggestion that the enzymes of the acetyl-CoA pathway in Clostridium thermoaceticum may assemble in vivo into multienzyme complexes [2] stems from the need to account for the differences in the rate of acetate synthesis attainable in vitro using isolated components as compared to the rate predicted in vivo during fermentation of glucose [3].…”
Section: Discussionmentioning
confidence: 99%
“…CoM methylation with methanol requires the methyltransferase MtaB and the corrinoid protein MtaC, which is then demethylated by another methylcobamide:CoM methyltransferase, MtaA (13)(14)(15). The methylation of CoM with methylated thiols such as dimethyl sulfide in Methanosarcina barkeri is catalyzed by a corrinoid protein that is methylated by dimethyl sulfide and demethylated by CoM, but in this case an associated CoM methylase carries out both methylation reactions (16).…”
mentioning
confidence: 99%
“…For the methanogen methylamine and methanol methyltransferase systems, an activation process is readily detectable in cell extracts that is ATP-and hydrogen-dependent (32,33). Daas et al (34,35) examined the activation of the methanol methyltransferase system in M. barkeri and purified in low yield a methyltransferase activation protein (MAP) which in the presence of a preparation of hydrogenase and uncharacterized proteins was required for ATP-dependent reductive activation of methanol:CoM methyl transfer.…”
mentioning
confidence: 99%
“…The central intermediate of methane formation from methanol is 2-(methylthio)ethanesulfonic acid (CH3-S-coenzyme M [CoM]) (19,39,43) which is reductively demrethylated with H2 to yield CH4 and 2-mercaptoethanesulfonic acid (CoM-SH) by the multicomponent methyl-coenzyme M methylreductase system (36, 37). Since the free energy change of this reaction (AG0' = -85 kJ/reaction) is large enough to drive ATP synthesis (9, 19), it has been hypothesized that one or several components of the methylreductase system are membrane associated and involved in proton translocation across the cytoplasmic membrane.…”
mentioning
confidence: 99%